Chief architect of Obamacare sparks furore over wish to "die at 75". (19th January 2015) - Lenzer, Jeanne
Abstract : Ezekiel Emanuel denies accusations that he supports euthanasia but says that the US should focus on quality not length of life, Jeanne Lenzer reports